Eine Theorie des lyrischen Gedichts - Dieter Lamping (Recherches Germaniques)
This essay proposes a theory of the lyrical poem which differs decisively from the traditional definition of poetry as metered speech. The essential statement of the theory is the definition of the lyrical poem as single speech in verse. In order to correspond to the conception of the lyrical genre in the understanding of Dieter Lamping a text has to meet two conditions: On the one hand the lyrical poem, a term which is employed synonymously to poetry, is to be distinguished from both dramatic and epic poems as it is considered as single speech in verses. On the other hand lyrical poems need to fulfill the formal criterion of composition in verses as well as the structural criterion of single speech. These criteria are related to the form of speech and the structure of speech. This minimal definition of lyrical texts as single speech in verses, which claims a constitutive interconnection between form and structure of speech, matches the aesthetic complexity and the plurality of poetry. It offers a universally valid description of poetry and a distinction of the lyrical poem from other types of poetic speech. In the end it provides in particular an appropriate approach to analyze modern poetry which disengages from the commitments of poetic traditions due to its pursuit of freedom.